What is a Pharmacist: Opinions of Pharmacy Department Academics and Community Pharmacists on Competences Required for Pharmacy Practice - Jeffrey Atkinson; Kristien de Paepe; Antonio Sánchez Pozo; Dimitrios Rekkas; Daisy Volmer; Jouni Hirvonen; Borut Bozic; Agnieska Skowron; Constantin Mircioiu; Annie Marcincal; Andries Koster; Keith Wilson; et al. (MDPI AG, 2016)
This paper looks at the opinions of 241 European academics (who provide pharmacy education), and of 258 European community pharmacists (who apply it), on competences for pharmacy practice. A proposal for competences was generated by a panel of experts using Delphi methodology. Once finalized, the proposal was then submitted to a large, European-wide community of academics and practicing pharmacists in an additional Delphi round. Academics and community pharmacy practitioners recognized the importance of the notion of patient care competences, underlining the nature of the pharmacist as a specialist of medicines. The survey revealed certain discrepancies. Academics placed substantial emphasis on research, pharmaceutical technology, regulatory aspects of quality, etc., but these were ranked much lower by community pharmacists who concentrated more on patient care competences. In a sub-analysis of the data, we evaluated how perceptions may have changed since the 1980s and the introduction of the notions of competence and pharmaceutical care. This was done by splitting both groups into respondents < 40 and > 40 years old. Results for the subgroups were essentially statistically the same but with some different qualitative tendencies. The results are discussed in the light of the different conceptions of the professional identity of the pharmacist.